Phenotypic and genetic characteristics in a cohort of patients with Usher genes - Feenstra, HM; Shah, M; Broadgate, S; Shanks, M; Kamath, A; Yu, J; Jolly, JK; MacLaren, RE; Clouston, P; Halford, S; Downes, SM (MDPI, 2022)
Background: This study aimed to compare phenotype–genotype correlation in patients with Usher syndrome (USH) to those with autosomal recessive retinitis pigmentosa (NS-ARRP) caused by genes associated with Usher syndrome. Methods: Case notes of patients with USH or NS-ARRP and a molecularly confirmed diagnosis in genes associated with Usher syndrome were reviewed. Phenotypic information, including the age of ocular symptoms, hearing impairment, visual acuity, Goldmann visual fields, fundus autofluorescence (FAF) imaging and spectral domain optical coherence tomography (OCT) imaging, was reviewed. The patients were divided into three genotype groups based on variant severity for genotype-phenotype correlations. Results: 39 patients with Usher syndrome and 33 patients with NS-ARRP and a molecular diagnosis in an Usher syndrome-related gene were identified. In the 39 patients diagnosed with Usher syndrome, a molecular diagnosis was confirmed as follows: USH2A (28), MYO7A (4), CDH23 (2), USH1C (2), GPR98/VLGR1 (2) and PCDH15 (1). All 33 patients with NS-ARRP had variants in USH2A. Further analysis was performed on the patients with USH2A variants. USH2A patients with syndromic features had an earlier mean age of symptom onset (17.9 vs. 31.7 years, p < 0.001), had more advanced changes on FAF imaging (p = 0.040) and were more likely to have cystoid macular oedema (p = 0.021) when compared to USH2A patients presenting with non-syndromic NS-ARRP. Self-reported late-onset hearing loss was identified in 33.3% of patients with NS-ARRP. Having a syndromic phenotype was associated with more severe USH2A variants (p < 0.001). Eighteen novel variants in genes associated with Usher syndrome were identified in this cohort. Conclusions: Patients with Usher syndrome, whatever the associated gene in this cohort, tended to have an earlier onset of retinal disease (other than GPR98/VLGR1) when compared to patients presenting with NS-ARRP. Analysis of genetic variants in USH2A, the commonest gene in our cohort, showed that patients with a more severe genotype were more likely to be diagnosed with USH compared to NS-ARRP. USH2A patients with syndromic features have an earlier onset of symptoms and more severe features on FAF and OCT imaging. However, a third of patients diagnosed with NS-ARRP developed later onset hearing loss. Eighteen novel variants in genes associated with Usher syndrome were identified in this cohort, thus expanding the genetic spectrum of known pathogenic variants. An accurate molecular diagnosis is important for diagnosis and prognosis and has become particularly relevant with the advent of potential therapies for Usher-related gene.